Power-Dependence Relations for Policy Formulation Gender Responsive Budgeting Case in West Sumatera Indonesia - Rozidateno Putri Hanida; Roy Valiant Salomo; Achmad Lutfi (Greenation International Journal of Law and Social Sciences, 2026)
While gender-responsive budgeting (GRB) aims to empower women, its execution often overlooks complex cultural landscapes. Addressing a critical research gap, this study moves beyond standard structural GRB assessments by examining its implementation within West Sumatra’s matrilineal society a unique context where women hold customary legitimacy but lack formal political influence. The novelty of this research lies in integrating policy network analysis with indigenous cultural paradigms to expose the exact disjuncture between symbolic gender authority and actual bureaucratic power. Through document analysis, interviews, and participatory observation, the study maps regional planning actors, revealing a narrow, hierarchical network. Power remains heavily concentrated among male bureaucrats and local parliaments, while women's organizations and civil society languish at the margins. This empirically confirms the "matrilineal paradox": customary female custodianship over lineage does not translate into formal political control, rendering local GRB merely administrative rather than transformative. The study makes a key theoretical contribution to feminist institutionalism and policy network theory by demonstrating how entrenched socio-cultural paradoxes can neutralize progressive fiscal policies. Ultimately, advancing GRB requires expanding policy networks to substantively integrate women’s and customary institutions, transforming budgeting from a performative task into genuine empowerment.